(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the manuscript sources of the literary heritage of Majzub Namangoni, a representative of the Namangan literary environment and a Sufi writer. It examines the preservation and condition of manuscript divans today and how the creative works of this author are presented within them.